From crisis management to long-term strategy - Hans-Eckart Scharrer (Intereconomics, 1975)
In view of the multitude of factors which are at work it is evident that there is no one-way solution to the current problems of the EC. Rather a differentiated approach is required. In this context it is essential that the long-term economic and political goals of the Community are not “forgotten” over the need to find pragmatic answers to present-day difficulties.
Keywords: 330; EC